ANALISIS STRATEGI PEMASARAN DIGITAL DALAM UPAYA PENINGKATAN OMSET PENJUALAN - Hesti Suryaning Tyasari; Finisica Dwijayati Patrikha (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
Geprek Bensu is a franchise business that offers contemporary food in the form of processed chicken with a variety of contemporary chili toppings owned by one of the Indonesian presenters, namely Ruben Onsu. Geprek Bensu began to be known to the wider community starting in early 2017, this did not escape the marketing strategy used by the owner by using digital promotion. With a strong branding, the brand can be recognized by the public very quickly. The purpose of this study is to analyze the digital marketing strategy used by Geprek Bensu in the city of Surabaya in an effort to increase sales turnover of Geprek Bensu. The method used in this study is a descriptive method with a sample of managers and employees from geprek bensu in the Surabaya city area. The sampling technique used observation and interview methods which were sent online. From the results of the study, it can be concluded that geprek bensu did a promotion on the digital ojol platform which was quite successful because of the large discounts that made spicy lovers consumers more interested in taking their orders home.